Vagal stimulation for control of complex partial seizures in medically refractory epileptic patients. - Wilder BJ; Uthman BM; Hammond EJ (Pacing & Clinical Electrophysiology, 1991)
Chronic intermittent stimulation of the vagus nerve is a new method currently being tested for the treatment of medically intractable complex partial seizures (CPS). We have studied the effects of vagal stimulation in nine patients with CPS for 4-16 months to determine its safety and efficacy. With the patients maintained on constant dosages of antiepileptic drugs, we recorded the electroen-cephalogram and electrocardiogram, and performed clinical laboratory tests and gastric analysis over a 6-week baseline period. The neurocybernetic prosthesis (NCP) was then implanted and connected to two spiral electrodes wound around the left vagus nerve. After a 4-week placebo period, vagal stimulation was started. Stimulation parameters were increased stepwise at monthly intervals until patients were being stimulated for 30-second periods at 20-50 Hz with 1-2 mA of current at 250-500-|micro;,sec pulses. A second 4-week placebo period was added 3 months after the implantation. Thereafter, vagal stimulation was resumed and self-stimulation with magnetic activation was allowed for a 1-minute period at the onset of an aura. Six patients had a significant reduction in the frequency, intensity, or duration of seizures. All patients tolerated the implantation and stimulation well and none reported pain, discomfort, or important changes in their daily activities, sleep habits, eating, swallowing, or breathing. There were no remarkable changes in blood pressure or heart rate.